Italy and the environmental humanities : landscapes, natures, ecologies - Iovino, Serenella; Cesaretti, Enrico; Past, Elena (Under the sign of nature., 2018)
Bringing together new writing by some of the field's most compelling voices from the United States and Europe, this is the first book to examine Italy--as a territory of both matter and imagination--through the lens of the environmental humanities. The contributors offer a wide spectrum of approaches--including ecocriticism, film studies, environmental history and sociology, eco-art, and animal and landscape studies--to move past cliche and reimagine Italy as a hybrid, plural, eloquent place. Among the topics investigated are post-seismic rubble and the stratifying geosocial layers of the Anthropocene, the landscape connections in the work of writers such as Calvino and Buzzati, the contaminated fields of the ecomafia's trafficking, Slow Food's gastronomy of liberation, poetic birds and historic forests, resident parasites, and nonhuman creatures. At a time when the tension between the local and the global requires that we reconsider our multiple roots and porous place-identities, Italy and the Environmental Humanities builds a creative critical discourse and offers a series of new voices that will enrich not just nationally oriented discussions, but the entire debate on environmental culture.